Responsive security : be ready to be secure - Kang, Meng-Chow (CRC Press/Taylor & Francis, 2014)
"Technology and business change along with information flows, vulnerabilities, exposures, and risks. Based on real-time practice experience, and research conducted by the author over the past decade, this book addresses the challenges, issues, and dilemmas of managing information security risk in a constantly changing business, technology, and operating environment. It introduces an approach, known as a Responsive Approach, for addressing these needs from both practitioner and organizational management perspectives"--